2016
DOI: 10.4103/0301-4738.178144
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic retinopathy in India: The All India Ophthalmological Society Diabetic Retinopathy Eye Screening Study 2014

Abstract: Aim:The aim of this study is to ascertain the prevalence of diabetic retinopathy (DR) in diabetic patients across the nation and attempt to establish history-based risk factors.Materials and Methods:A cross-sectional study of diabetic patients was conducted as an initiative of the All India Ophthalmological Society from 14th November to 21st November 2014. Known diabetics were evaluated voluntarily by members of the society at 194 centers using a structured protocol provided by the society for examination. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
123
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 20 publications
7
123
7
1
Order By: Relevance
“…But some studies have suggested that South Asians are more likely to have DR as compared to white Europeans, but Asians with DR are younger, the course of disease is short, blood pressure and plasma sugar level are higher [9]. Although there is no ethnic difference among Asian countries, [10] the prevalence observed in our study is far higher than in other Asian countries such as India (21.7%) [11] and Bangladesh (21.6%) [12] but lower than Singapore(35%) [13]. These differences among studies may be caused by the type of study population, the sample size, age of the patients, different methods of fundus evaluation and the average levels of various variables.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…But some studies have suggested that South Asians are more likely to have DR as compared to white Europeans, but Asians with DR are younger, the course of disease is short, blood pressure and plasma sugar level are higher [9]. Although there is no ethnic difference among Asian countries, [10] the prevalence observed in our study is far higher than in other Asian countries such as India (21.7%) [11] and Bangladesh (21.6%) [12] but lower than Singapore(35%) [13]. These differences among studies may be caused by the type of study population, the sample size, age of the patients, different methods of fundus evaluation and the average levels of various variables.…”
Section: Discussioncontrasting
confidence: 62%
“…Cr.) were studied in various literatures [3,8,9,[11][12][13][14][15][16]. There is 29 times higher risk to develop blindness due to diabetic retinopathy than non-diabetic of similar age and gender [4].…”
Section: Introductionmentioning
confidence: 99%
“…In present study there were 20 cases (55.5%) having NPDR, 9 cases (25%) have PDR, and 7 cases (19.3%) with diabetic maculopathy. The prevalence in the AIOS study was 21.27% with a range of 12.27% in the central zone and 34.06% in the north zone in India [7]. Prevalence of diabetic retinopathy was estimated up to 18% in urban population of India [8].…”
Section: Discussionmentioning
confidence: 92%
“…According to WHO 70 million people were affected by diabetes in India in the year 2015 and the figure is estimated to rise to 79.4 million by 2030. 1 Diabetes Mellitus is a chronic metabolic disorder characterized by hyperglycaemia and disturbances in carbohydrate, fat and protein metabolism caused by defects in insulin secretion, action or both. 2 There are mainly three types of diabetes: Type 1 diabetes, Type 2 diabetes including a related condition called pre-diabetes and gestational diabetes.…”
Section: Introductionmentioning
confidence: 99%